2015
DOI: 10.1111/lic3.12230
|View full text |Cite
|
Sign up to set email alerts
|

Inside Out, Outside In: Thinking a Tagorean Future of Education

Abstract: Rabindranath Tagore's ideas can still inspire education in the East as well as in the West today. In this paper, I survey Tagore's philosophical anthropology and argue that there is more coherence to his philosophy and pedagogy than is usually seen. For Tagore, the highest goal is to make the world one's own, as well as to enlarge one's self to encompass the world. The educational practices through which this ideal can be reached can be classified as "creative action," "love," and "freedom." On the basis of su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Some studies have suggested that the approach may have potential benefits in terms of promoting creativity, critical thinking, and holistic development of the individual [32]. For example, a study conducted found that the Tagorean approach to education was effective in promoting creativity among primary school students in India [33].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have suggested that the approach may have potential benefits in terms of promoting creativity, critical thinking, and holistic development of the individual [32]. For example, a study conducted found that the Tagorean approach to education was effective in promoting creativity among primary school students in India [33].…”
Section: Introductionmentioning
confidence: 99%